Pengaruh Instagram dan EWOM Terhadap Minat dan Keputusan Pembelian Konsumen Produk Skincare - Maria Anita Carolina Kioek; Lena Ellitan; Yuliasti Ika Handayani (BIP's JURNAL BISNIS PERSPEKTIF, 2022)
This study further finds out about the influence of instagram social media and electronic word of mouth (EWOM) as promotional media on buying interest and consumer purchase decisions on Somethinc skincare products. The sampling technique used is non-probability sampling by purposive sampling. As for the background of this research is the role of the use of social media Instagram and how influential electronic word of mouth (EWOM) on buying interest and consumer purchasing decisions. The research was conducted for skincare products with the SomeThinc brand. The sampling technique used is nonprobability sampling by purposive sampling. The sample used in this study were 105 respondents. The respondents in this study were required to be at least 17 years old, have an instagram social media account and have purchased SomeThinc skincare products. The data analysis technique used is SEM-PLS analysis using the SmartPLS 3.0 program. The results of this study indicate that instagram social media has a significant effect on buying interest, instagram social media has a significant effect on consumer purchasing decisions, electronic word of mouth (EWOM) has a significant effect on buying interest, electronicword of mouth (EWOM) has an effect on consumer purchasing decisions, buying interest has a significant effect on consumer purchasing decisions, social media instagram has a significant effect on consumer purchasing decisions mediated by buying interest, electronic word of mouth (EWOM) has a significant effect on consumer purchasing decisions mediated by buying interest.